2022
DOI: 10.4067/s1726-569x2022000100125
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining informed consent: psychiatric nurses’ knowledge and practice at federal neuropsychiatric hospital Enugu, Nigeria

Abstract: Background: Within a psychiatric care setting, informed consent is the voluntary acceptance of a plan for medical care by a competent patient after full disclosure of the care plan, its risks, benefits, and alternative approaches. This implies that the patient must have full information about any treatment options and must be competent to make the needed decisions. Objective: To assess psychiatric nurses' knowledge and practices of obtaining informed consent. Research Method: The study used a quantitative, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…However, in study conducted by Chinwe in NIGERIA found that the vast majority of participants (94.8%) were aware of the legal and ethical implications of informed consent. (Chinwe S. F. Ezeruigbo, 2022) This study reveals that half of the participants were knowledgeable about informed consent but a survey carried out by Chinwe shows affirmed knowledge about informed consent. (Chinwe S. F. Ezeruigbo, 2022) The present study found that the majority of participants were aware mental status is an important indicator of the ability to consent this finding is similar to a survey done by Chima in South Africa which found that most nurses in the study were aware of that and used routine mental status examinations to assess patients' competence.…”
Section: Table (2)mentioning
confidence: 70%
See 2 more Smart Citations
“…However, in study conducted by Chinwe in NIGERIA found that the vast majority of participants (94.8%) were aware of the legal and ethical implications of informed consent. (Chinwe S. F. Ezeruigbo, 2022) This study reveals that half of the participants were knowledgeable about informed consent but a survey carried out by Chinwe shows affirmed knowledge about informed consent. (Chinwe S. F. Ezeruigbo, 2022) The present study found that the majority of participants were aware mental status is an important indicator of the ability to consent this finding is similar to a survey done by Chima in South Africa which found that most nurses in the study were aware of that and used routine mental status examinations to assess patients' competence.…”
Section: Table (2)mentioning
confidence: 70%
“…(Chinwe S. F. Ezeruigbo, 2022) This study reveals that half of the participants were knowledgeable about informed consent but a survey carried out by Chinwe shows affirmed knowledge about informed consent. (Chinwe S. F. Ezeruigbo, 2022) The present study found that the majority of participants were aware mental status is an important indicator of the ability to consent this finding is similar to a survey done by Chima in South Africa which found that most nurses in the study were aware of that and used routine mental status examinations to assess patients' competence. (Chima, 2022) According to this study, most of the participants spend between five and fifteen minutes on average, explaining all the facts the patient needs to know before signing the surgical consent.…”
Section: Table (2)mentioning
confidence: 70%
See 1 more Smart Citation